1987
DOI: 10.1007/bf00165562
|View full text |Cite
|
Sign up to set email alerts
|

Mechanographic analysis of muscle rigidity after morphine and haloperidol: a new methodological approach

Abstract: The new method described in this study was based on consecutive repeated measurements of the resistance of flexor and extensor muscles of the hind foot of the rat to forced flexions and extensions of the foot. Locomotor movements of the rat were restrained with a metaplex box which had a slot for the hind limb. The control muscle tone measured by this method was constant for more than 2 h, and amounted to approx. 25 g for flexor muscles, and approx. 45 g for extensors. Morphine (2.5, 5, 10, 20 mg/kg) enhanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…A similar effect was obtained by , who used a mechanomyographic method of measuring the muscular rigidity. By this method one can measure the resistance of the rat's hind limb in response to an imposed bending and straightening in the ankle joint (Kolasiewicz et al, 1987). This resistance is accepted as muscular rigidity.…”
Section: The Effect Of Nmda Receptor Antagonists On the Neuroleptic-amentioning
confidence: 99%
“…A similar effect was obtained by , who used a mechanomyographic method of measuring the muscular rigidity. By this method one can measure the resistance of the rat's hind limb in response to an imposed bending and straightening in the ankle joint (Kolasiewicz et al, 1987). This resistance is accepted as muscular rigidity.…”
Section: The Effect Of Nmda Receptor Antagonists On the Neuroleptic-amentioning
confidence: 99%
“…The results presented show that rats respond with increasing resistance to passive flexion or extension of the hindfeet. Our previous experiments demonstrated that such resistance is a reliable measure of muscle tone (Kolasiewicz et al 1987;Ossowska et al 1992Ossowska et al , 1994Wolfarth et al 1992;Lorenc-Koci et al 1994). The maximum resistance (MMGmax) observed in normal, young animals was significantly greater during flexion than during extension (Kolasiewicz et al 1987;Wolfarth et al 1992; present results) presumably because the gastrocnemius muscle (which is stretched during flexion) is larger than the tibialis anterior muscle (which is stretched during extension).…”
Section: Electromyogrammentioning
confidence: 98%
“…Our previous experiments demonstrated that such resistance is a reliable measure of muscle tone (Kolasiewicz et al 1987;Ossowska et al 1992Ossowska et al , 1994Wolfarth et al 1992;Lorenc-Koci et al 1994). The maximum resistance (MMGmax) observed in normal, young animals was significantly greater during flexion than during extension (Kolasiewicz et al 1987;Wolfarth et al 1992; present results) presumably because the gastrocnemius muscle (which is stretched during flexion) is larger than the tibialis anterior muscle (which is stretched during extension). The appearance of short-and long-latency components of the reflex EMG activity in response to the stretching of different muscles has been well documented in humans (Marsden et al 1973; Lee & Tatton, 1975;Berardelli et al 1983;Rothwell et al 1983;Tatton et al 1984;Scholz et al 1987;Lee, 1989;Bergui et al 1992; for reviews see Matthews, 1991;Davidoff, 1992) and primates (Lee & Tatton, 1975; for review see Matthews, 1991).…”
Section: Electromyogrammentioning
confidence: 98%
See 2 more Smart Citations